Aggregation propensity of Aib homo‐peptides of different length: an insight from molecular dynamics simulations‡. (20th May 2014) - Bocchinfuso, Gianfranco; Conflitti, Paolo; Raniolo, Stefano; Caruso, Mario; Mazzuca, Claudia; Gatto, Emanuela; Placidi, Ernesto; Formaggio, Fernando; Toniolo, Claudio; Venanzi, Mariano; Palleschi, Antonio; Morelli, Giancarlo; et al.
<x xml:space="preserve">Abstract</x> Interactions between peptides are relevant from a biomedical point of view, in particular for the role played by their aggregates in different important pathologies, and also because peptide aggregates represent promising scaffolds for innovative materials. In the present article, the aggregation properties of the homo‐peptides formed by α‐aminoisobutyric acid (U) residues are discussed. The peptides investigated have chain lengths between six and 15 residues and comprise benzyl and naphthyl groups at the N‐ and C‐termini, respectively. Spectroscopic experiments and molecular dynamics simulations show that the shortest homo‐peptide, constituted by six U, does not exhibit any tendency to aggregate under the conditions examined. On the other hand, the homologous peptide with 15 U forms very stable and compact aggregates in 70/30(v/v) methanol/water solution. Atomic force microscopy images indicate that these aggregates promote formation of long fibrils once they are deposited on a mica surface. The aggregation phenomenon is mainly due to hydrophobic interactions occurring between very stable helical structures, and the aromatic groups in the peptides seem to play a minor role. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.